2020
DOI: 10.3390/su12135266
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Behavioral Intention to Engage in Environmental Accounting Practices for Corporate Sustainability: Managerial Perspectives from a Developing Country

Abstract: Environmental degradation is a serious global issue that has received increasing attention from scholars, policymakers, regulators, environmental activists, and the public as a whole. In the meantime, corporations have been criticized as major contributors to environmental pollution. Environmental accounting (EA) is a corporate practice that seeks to account for the cost of environmental impacts of business operations. However, it is questionable whether the true cost of environmental impacts of business opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 76 publications
(129 reference statements)
1
4
0
Order By: Relevance
“…Finally, the path analysis underlined that BI had a positive and significant effect on EP ( H8 was accepted). Likewise, such consequences are consistent with the findings of previous studies by Darnall and Sides (2008), He (2020) and Chen et al (2020), who claimed BIs’ predictive power of BIs towards EP and environmental sustainability (Swaim et al , 2013). These usually happen through the TPB theory.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Finally, the path analysis underlined that BI had a positive and significant effect on EP ( H8 was accepted). Likewise, such consequences are consistent with the findings of previous studies by Darnall and Sides (2008), He (2020) and Chen et al (2020), who claimed BIs’ predictive power of BIs towards EP and environmental sustainability (Swaim et al , 2013). These usually happen through the TPB theory.…”
Section: Discussionsupporting
confidence: 92%
“…Using the theory of planned behaviour (TPB), factors such as subjective norms, attitudes towards behaviour and personal control significantly predict the BIs and environmental sustainability (Swaim et al , 2013). According to Chen et al (2020), environmental accounting attitudes considerably affect BIs. When companies are confronted by market pressure, they are likely to consider their pro-environmental behaviours.…”
Section: Literature Review and Conceptualizationmentioning
confidence: 99%
“…Therefore, we used a PLS-SEM approach using Smart PLS 3 software in our data analysis and model evaluation. More recently, PLS-SEM has widely been used in various studies in different disciplines such as Total Quality Management, IT, Environmental Accounting, Finance, and particularly in Marketing, relative to covariance-based SEM (CB-SEM) (see, for example, [64][65][66][67]). This is because PLS-SEM is capable of handling complex models, and because of its high statistical power and flexibility in parametric assumption and sample size [68,69].…”
Section: Discussionmentioning
confidence: 99%
“…We also assessed the multi-collinearity of exogenous latent constructs with respect to their endogenous latent construct in the structural model and the results of which is presented in Table 6. The VIF values below 5 are indicative of the absence of multi-collinearity issue in the empirical model [66].…”
Section: The Assessment Of the Measurement Modelmentioning
confidence: 99%
“…Diaz, M. A. H. et al revealed the application of the ecological full-cost accounting analysis framework to the treatment of chemical wood products and concrete crossover, which resulted in the selection of the lowest environmental cost concrete and furfural landfill treatments after comparative analysis of combustion and landfill treatments [9]. Chen, X. et al examined the reasons behind engaging in ecological accounting in Sri Lanka, and the findings stated that it was due to the fact that managers significantly felt the positive impact of EA practices, which included subjective norms and perceived behavioral control [10]. Cheng, H. et al studied the association between corporate production behavior and environmental accounting behavior based on data from 253 Chinese firms.…”
Section: Introductionmentioning
confidence: 99%